Debt Report 2021 Edition I - World Bank Group (Washington, DC: World Bank, 2021)
This is the first of the series of debt reports for 2021 to be published online, at regular intervals, over the course of the year. Their aim is to provide users with analyses of evolving trends and development related to external debt and public debt in individual countries and regional groups, with primary emphasis on low- and middle-income countries, and to keep users abreast of debt-related issues and initiatives. This report presents a summary analysis of the composition of external debt stocks and flows from a regional perspective and draws out the main messages of the regional and country specific data.